Real Time Implementation of Increasing Torque using Mechanical Gear in Bldc Motor - et. al., Dr. R. Satheesh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In present days, universally air contamination of the atmosphere is predominately increasing in the biosphere; due to toxic emission like CO, NOx and SO2.Internal combustion engines is one of the major sources of air contamination, by this the properties of fossil fuel emissions and address environmental concerns (ECs) should be mitigated. Now a days, E-vehicles are emerging all over the globe and many nations encourage the people to use EVs. Previous studies show that the many of the consumers are anxiety, because of two reasons: one is due to cost of E-vehicle and other is charging stations are not available in India. The vision of the Indian Government in 2030, all the vehicles are replaced by ‘Electric Vehicles’ on Road. In this article, emphasis to increases the motor torque using gear. In this type of gear arrangement will helps to easy carrying the goods smoothly for all the conditions.